2014
DOI: 10.1128/aac.03595-14
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rift Valley Fever Virus Replication and Perturbation of Nucleocapsid-RNA Interactions by Suramin

Abstract: Rift Valley fever virus (RVFV) is an emerging infectious pathogen that causes severe disease in humans and livestock and has the potential for global spread. There are currently no proven safe and effective treatment options for RVFV infection. Inhibition of RNA binding to RVFV nucleocapsid protein (N) represents an attractive antiviral therapeutic strategy because several essential steps in the RVFV replication cycle involve N binding to viral RNA. In this study, we demonstrate the therapeutic potential of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…The interference of viral protein − RNA interactions have been addressed also by small RNA molecules (aptamers) or compounds (Suramin) that can block RNA binding sites of the nucleoproteins with potential antiviral effect. This have been explored for RVFV NP and similar approaches could be undertaken now towards the L protein − vRNA specific binding sites based on the available structures for the in silico design of interfering compounds and aptamers and using the high-throughput fluorescence-based methods available for the study of L protein vRNA interactions (Ellenbecker et al, 2015(Ellenbecker et al, , 2014Gerlach et al, 2015).…”
Section: Development Of New Antiviral Drugs Targeting the Activity VImentioning
confidence: 99%
“…The interference of viral protein − RNA interactions have been addressed also by small RNA molecules (aptamers) or compounds (Suramin) that can block RNA binding sites of the nucleoproteins with potential antiviral effect. This have been explored for RVFV NP and similar approaches could be undertaken now towards the L protein − vRNA specific binding sites based on the available structures for the in silico design of interfering compounds and aptamers and using the high-throughput fluorescence-based methods available for the study of L protein vRNA interactions (Ellenbecker et al, 2015(Ellenbecker et al, , 2014Gerlach et al, 2015).…”
Section: Development Of New Antiviral Drugs Targeting the Activity VImentioning
confidence: 99%
“…actually due to its inhibitory effect on the interaction between the viral gp120 and the CD4 receptor (Schols et al, 1990). Suramin has also been shown to block the binding or early steps of infection of several DNA and RNA viruses, like herpes simplex virus type-1 (Aguilar et al, 1999), cytomegalovirus (Baba et al, 1993), human hepatitis B virus (Schulze et al, 2007), hepatitis delta virus (Petcu et al, 1988), hepatitis C virus (Garson et al, 1999), dengue virus (Chen et al, 1997), several bunyaviruses (Crance et al, 1997;Ellenbecker et al, 2014;Iqbal et al, 2000;Jiao et al, 2013), norovirus-like particles (Tamura et al, 2004) and enterovirus 71 (Wang et al, 2014), for which the antiviral activity of suramin was also confirmed in an animal model (Ren et al, 2014). In recent in vitro studies suramin was identified as a hepatis C virus and dengue virus helicase inhibitor (Basavannacharya and Vasudevan, 2014;Mukherjee et al, 2012) and also as a norovirus RdRp inhibitor by virtual screening and biochemical assays with purified enzymes (Mastrangelo et al, 2012;Tarantino et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the aptamer RNAs competitively bind to N in infected cells, and thereby interfere with N’s normal functions in viral replication. Nucleocapsid protein has been regarded as a potential antiviral target in many viruses [912], these results emphasize that perturbing N function is an effective way to inhibit viral replication.…”
Section: Discussionmentioning
confidence: 99%